The phenomenon of fear of missing out (FOMO) on tiktok application users with an analysis of Islamic educational psychology perspectives among Trunojoyo Madura University Students - Selvina Apriyanti; Qoniah Nur Wijayani (Edusoshum : Journal of Islamic Education and Social Humanities, 2024)
Various social media platforms have emerged by offering various interesting features for smartphones, one of which is the TikTok app, with a high download rate. This study aims to understand the impact of FoMO on TikTok users and see how the perspective of Islamic educational psychology can provide additional insights related to this phenomenon. The research method includes surveys and qualitative data analysis, focusing on students' behavior patterns and perceptions of FoMO in the context of TikTok use. The results of the study explained that the availability of interesting features in the Tiktok application causes users to often forget the time in accessing, excessive use of social media can cause the phenomenon of Fear of Missing Out. Fear of Missing Out (FoMO) is a psychological behavior when a person feels that he misses important trends, moments, and information expressed by others, so they experience feelings of anxiety or fear of missing the moment. Overuse of TikTok can disrupt sleep, cause eye disorders, and affect posture. Solutions from the perspective of Islamic educational psychology involve developing self-understanding, self-control, and maintaining life balance in accordance with religious values to create more positive and meaningful digital experiences.